Challenges and Opportunities for Integrated Modeling of Climate Engineering - Massimo Tavoni; Valentina Bosetti; Soheil Shayegh; Laurent Drouet; Johannes Emmerling; Sabine Fuß; Timo Goeschl; Celine Guivarch; Thomas S. Lontzek; Vassiliki Manoussi; Juan Moreno Cruz; Helene Muri; et al. (Fondazione Eni Enrico Mattei (FEEM), 2017)
The Paris Agreement has set stringent temperature targets to limit global warming to 2°C above preindustrial level, with efforts to stay well below 2°C. At the same time, its bottom-up approach with voluntary national contributions makes the implementation of these ambitious targets particularly challenging. Climate engineering – both through carbon dioxide removal (CDR) and solar radiation management (SRM) – is currently discussed to potentially complement mitigation and adaptation. Results from integrated assessment models already suggest a significant role for some forms of climate engineering in achieving stringent climate objectives1. However, these estimates and their underlying assumptions are uncertain and currently heavily debated2–4. By reviewing the existing literature and reporting the views of experts, we identify research gaps and priorities for improving the integrated assessment of climate engineering. Results point to differentiated roles of CDR and SRM as complementary strategies to the traditional ones, as well as diverse challenges for an adequate representation in integrated assessment models. We identify potential synergies for model development which can help better represent mitigation and adaptation challenges, as well as climate engineering.
Keywords: Q5; Q55; 330; Climate Engineering; Paris Agreement; Carbon Dioxide Removal; Solar Radiation Management; Integrated Assessment Models